The effect of blended learning on students' learning outcomes in history education - Alfarez, Sidqi; Marta, Nur'aeni; Setiawan, Risky (Program Pascasarjana Universitas Negeri Yogyakarta, 2024)
Learning in the new average era presents challenges and opportunities, particularly in implementing blended learning in teaching and learning processes. This study aims to analyze the effect of blended learning implementation on students' learning outcomes in history education at SMA Negeri 89 Jakarta and evaluate its effectiveness in the cognitive, psychomotor, and affective domains. The research employed a quantitative approach with an ex post facto design. Data were collected through questionnaires and documentation, while data analysis was conducted using Pearson correlation to measure the relationships between variables and simple linear regression to determine the impact. The results show a significant positive effect of blended learning implementation on students' learning outcomes. A correlation value of 0.345 supports this finding, with a simple linear regression test indicating that the calculated r-value (3.446) exceeds the table r-value (1.987), thus accepting the alternative hypothesis. Students' cognitive and psychomotor aspects showed significant improvement, with an average score of 87. In contrast, the affective aspect, encompassing spiritual and social attitudes, reflected good behaviour among grade XI social studies students. These findings affirm that blended learning effectively improves students' learning outcomes by integrating technology with traditional approaches. The strength of blended learning lies in its flexibility and potential to create interactive and immersive learning experiences. This study provides significant insights, emphasizing the crucial role of educators and education policymakers in adopting innovative learning strategies to enhance the quality of education in the digital era.